THE CONTROL MECHANISM OF PASSENGER CARS PARKS - Karas, O. O. (Science and Transport Progress, 2008)
In the article the technique of calculation of wagon stocks taking into account their writing off, renovating, taking off for economic needs and implementing the structural reform is presented.